1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<531::aid-jbm13>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors which affect the calcification of tissue‐derived bioprostheses

Abstract: Mineralization of implanted bioprostheses poses a major clinical problem. Crosslinking of collagenous matrices, a process used to render tissues relatively inert and nonbiodegradable, seems to encourage calcification. Residual, noncovalently bound glutaraldehyde, as well as glutaraldehyde crosslinks which can be degraded with time, seem to play a role in this connection.Our findings demonstrate the need to carefully remove noncovalently or labile-associated glutaraldehyde by thorough rinsing or neutralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…bioprosthetic heart valves and aortic homografts). Besides crosslinked cellular debris, elastin and collagen may serve as nucleation sites for mineralisation, independent of cellular components [100][101][102]. Calcifi cation may be genetically controlled by molecules that actively inhibit calcifi cation and may occur passively when these inhibitors are absent [103].…”
Section: Elastin As a Biomaterialsmentioning
confidence: 99%
“…bioprosthetic heart valves and aortic homografts). Besides crosslinked cellular debris, elastin and collagen may serve as nucleation sites for mineralisation, independent of cellular components [100][101][102]. Calcifi cation may be genetically controlled by molecules that actively inhibit calcifi cation and may occur passively when these inhibitors are absent [103].…”
Section: Elastin As a Biomaterialsmentioning
confidence: 99%
“…In addition, the devitalized nature of BPHVs after glutaraldehyde treatment prevents any cellmediated remodeling of the extracellular matrix (ECM) that would otherwise maintain GAG concentrations. 1,5 The implications of this have been demonstrated in clinically retrieved BPHVs derived from glutaraldehyde-crosslinked porcine aortic cusps, which exhibit decreased levels of GAG molecules. 4 Reduction in cuspal GAG concentrations has also been shown in rheumatic and aged valves, both of which are highly prone to failure.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of bioprosthetic valves, usually made from porcine and bovine heart tissues, besides the already mentioned factors, calcification is also related to the valve treatment before implantation (4)(5)(6)(7). The stabilization of tissues by glutaraldehyde promotes cell death, and it has been demonstrated that its activity persists for many months, slowly liberating active glutaraldehyde monomers, causing the death of host fibrocytes and macrophages that come into contact with the toxic valve material (1).…”
mentioning
confidence: 99%